TEKNIK EDITING FLASHING LIGHT PADA ADEGAN AKHIR FILM PENGABDI SETAN 2: COMMUNION (2022) KARYA JOKO ANWAR - Beni Pusanding Tuah Beni Tuah; I Wayan Nain Febri (Universitas Dinamika, 2026)
Horror films are widely known for their ability to create fear through darkness, suspenseful sound, and visual shocks. One common technique is the use of limited lighting, such as flashing lights, combined with editing strategies. This study examines the final scene in Pengabdi Setan 2: Communion (2022), which employs flashing light as the central element to intensify the horror effect. The focus of this research is on how editing through cutting rhythm, shot duration, and cut to black, organizes the flashing light to produce tension and surprise for the audience. Using film textual analysis and Eisenstein’s montage theory, this study explores how editing patterns synchronized with pulsating light intervals create visual disorientation and distinctive shock effects. The findings show that rapid editing, dominated by medium to close-up shots combined with flashing light, successfully produces a claustrophobic atmosphere and layered tension. This technique also strengthens the visual narrative by presenting horror through the “uncertainty of vision,” making it difficult for viewers to predict what will appear next. Thus, flashing light is not merely a diegetic light source in the story but becomes an essential part of the editing technique that constructs immersive horror. This study concludes that Joko Anwar enriches Indonesian horror aesthetics by merging light and editing into a unified visual style.